(untitled) (Annals of Medical Research, 2021)
Aim: Local anesthetics are commonly used in surgical interventions and anesthesia applications. The aim of this study was to increase the sensitivity of local anesthetic toxicity to the presence of symptoms, precautions to be taken and the use of 20% lipid infusion for treatment. Material and Methods: The questionnaire was applied on 160 of 205 physicians who were prescribed local anesthetics.Results: Of the 160 participants included in the study, 108 (67.5%) were research assistants, 47 (29.4%) were faculty members and the remaining 5 (3.1%) were expert medical practitioners. 63 of the participants (39.4%) had been working in the medical profession for more than 5 years. While 42.5% of the participants administered local anesthetics every day, 33.1% had not received any training in the area. On the basis of their training status, it was the anesthetists among specialist doctors who were the most trained in anesthetics with a statistically high rate of 86.3%. Thirty-three of the surveyed physicians (20.6%) who responded stated that they had experienced a case of local anesthetic toxicity previously. The most frequent answer to the question in early findings concerning local anesthetic toxicity was anaphylaxis (74.4%). 38.1% of the participants had not heard the use of 20% lipid solution in local anesthetic toxicity. Although there was 20% lipid solution in the university hospital where the research was conducted, 31.9% of the participants knew this.Conclusion: Although local anesthetic toxicity is rare, it frequently occurs in clinical practice. Therefore, physicians should have general knowledge regarding local anesthetic drugs, maximum doses, side effects, toxicity symptoms and the required treatment in the case of toxicity. We also think local anesthetic toxicity should be included in annual training programs and practical applications by other clinical branches that apply local anesthetic drugs as we currently do at our Clinic and physicians should be given appropriate guidance.